How reliable are amygdala findings in psychopathy? A systematic review of MRI studies. (November 2022) - Deming, Philip; Heilicher, Mickela; Koenigs, Michael
Abstract: The amygdala is a key component in predominant neural circuitry models of psychopathy. Yet, after two decades of neuroimaging research on psychopathy, the reproducibility of amygdala findings is questionable. We systematically reviewed MRI studies (81 of adults, 53 of juveniles) to determine the consistency of amygdala findings across studies, as well as within specific types of experimental tasks, community versus forensic populations, and the lowest- versus highest-powered studies. Three primary findings emerged. First, the majority of studies found null relationships between psychopathy and amygdala structure and function, even in the context of theoretically relevant tasks. Second, findings of reduced amygdala activity were more common in studies with low compared to high statistical power. Third, the majority of peak coordinates of reduced amygdala activity did not fall primarily within the anatomical bounds of the amygdala. Collectively, these findings demonstrate significant gaps in the empirical support for the theorized role of the amygdala in psychopathy and indicate the need for novel research perspectives and approaches in this field. Graphical Abstract: ga1 Highlights: Reviewed 134 MRI studies of relationships between amygdala and psychopathy. Null relationships more common than significant positive or negative relationships. Negative relationships more common for studies with low power. Many peak coordinates labeled "amygdala" in original paper outside the amygdala.